CAD and GIS integration - Karimi, Hassan A.; Akinci, Burcu (Boca Raton : CRC Press, 2010)
"From early developments to current trends and future directions, th is concise resource allows you to get up to speed quickly on what it ta kes to get the most from these two dynamic technologies. Numerous examp le applications of effective CAD/GIS integration provide the understand ing needed to improve designs, make better decisions, and reduce or eve n eliminate costly errors in your next project."--BOOK JACKET.
Current trends and future directions in CAD / Omer Akin -- Current t rends and future directions in GIS / Piyawan Kasemsuppakorn, Duangduen Roongpiboonsopit, and Hassan A. Karimi -- CAD/GIS integration : rationa le and challenges / Omer Akin -- Interoperable methodologies and techni ques in CAD / Semiha Kiziltas ... [et al.] -- Interoperable methodologi es and techniques in CAD-GIS integration standardization efforts : the open geospatial consortium perspective / Carl Reed -- CAD/GIS integrati on issues for seamless navigation between indoor and outdoor environmen ts / Mahsa Ghafourian and Hassan A. Karimi -- Semantics in CAD/GIS inte gration / Michael J. Casey and Sriharsha Vankadara -- Ontologies for li nking CAD/GIS / Tamer el-Diraby and Hesham Osman -- CAD and GIS interop erability through semantic web services / Burcu Akinci ... [et al.].
"An Auerbach book."
Includes bibliographical references and index.
Keywords: Geographic information systems -- Computer-aided design; Geography -- Mathematical models -- Computer-aided design; Software compatibility